THE EFFECT OF LEVEL LINING SYSTEM TRAINING ON LEAD CLIMBING SCORE ACHIEVEMENT OF MAPALA SUMEDANG MEMBERS - Putri, Meyra Hernanda; Suherman, Ayi; Saptani, Entan (Universitas Negeri Medan, 2023)
Natural rock climbing (climbing) and wall climbing (wall climbing) The lead category is one of the groups or classes that compete in wall climbing sports by taking a predetermined route with a certain level of difficulty (grade). The research method uses an experimental method with a pre-experimental design, purposive random sampling data collection with 10 samples taken from mapala members of Sumedang Regency. Data from the experimental and control groups as well as the pretest and posttest show that the Shapiro Wilk sig value is 0.05, so the conclusion from this distribution is that it is normal. It can be concluded that the magnitude of the difference in changes in each group is proven by an increase in the LLS group of 07.20 and the regular training group of 05.60. This training model can be applied as training for beginners. It is recommended for future researchers to use larger samples.